2009
DOI: 10.1007/s10535-009-0011-5
|View full text |Cite
|
Sign up to set email alerts
|

Waterlogging induced oxidative stress and antioxidant activity in pigeonpea genotypes

Abstract: The objective of this study was to examine the role of antioxidant enzymes in waterlogging tolerance of pigeonpea (Cajanus cajan L. Halls) genotypes ICP 301 (tolerant) and Pusa 207 (susceptible). Waterlogging resulted in visible yellowing and senescence of leaves, decrease in leaf area, dry matter, relative water content and chlorophyll content in leaves, and membrane stability index in roots and leaves. The decline in all parameters was greater in Pusa 207 than ICP 301. Oxidative stress in the form of superox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
64
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(76 citation statements)
references
References 49 publications
11
64
1
Order By: Relevance
“…RNA blot analysis confirmed that the induction of O 2 regulated genes was related to antioxidative mechanism. Hypoxia induced increase in the transcripts of Cu/Zn-SOD and APX have also been reported in pigeon pea (Kumutha et al 2009;Sairam et al 2009b).…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…RNA blot analysis confirmed that the induction of O 2 regulated genes was related to antioxidative mechanism. Hypoxia induced increase in the transcripts of Cu/Zn-SOD and APX have also been reported in pigeon pea (Kumutha et al 2009;Sairam et al 2009b).…”
Section: Discussionmentioning
confidence: 69%
“…Further, the rise in ROS from 4th to 8th day of water-logging treatment could be due to the induction of membrane linked NADPH oxidase. Water-logging induced increase in the activity of diphenylene iodonium chloride-sensitive NADPH oxidase dependent superoxide production as well as increase in the expression of NADPH oxidase has been reported in pigeon pea (Kumutha et al 2009 andSairam et al 2009b). Blokhina et al (2001) reported H 2 O 2 formation during anoxia as evidenced by electron dense insoluble precipitate of cerium perhydroxide, visualized through electron microscope.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Higher GR activity was also reported in crop plants like wheat, sorghum, pigeon pea and foxtail millet [14][15][16]17]. The efficiency of antioxidant enzymes determines the amount of dehydration-induced H2O2 in plant cell [18].…”
Section: Discussionmentioning
confidence: 85%